Effect of specimen size and shape on compressive strength of foamed concrete containing kenaf fiber - Qumaysh, Adeb Abobakr Mohammed (2019)
Present research studies the effects of specimen size and shape on compressive strength of foamed concrete. There are two mixtures of foamed concrete (FC) and foamed concrete containing kenaf fiber (KFC). All specimens were tested to determine the compressive strength and workability of foamed concrete. The size and shape of specimens used for compressive strength were cubes of size 150 x 150 x 150 mm, 100 x 100 x 100 mm and 50 x 50 x 50 mm and cylinders of 150 x 300 mm and 100 x 200 mm. The mix density was design as 1600 kg/m3. From the experimental results, both mixtures showed increases in the compressive strength for all sizes and shape of specimens form 7 days to 28 days. As compared to FC mix, the KFC mix generate higher compressive strength about 12 MPa in cube size 150mm x 150mm x150mm at 28 day and achieved 10 MPa at 28 day in cylinders size 150mm x300mm.